Odesan Parisians: The Phenomenon of the Ukrainian Diaspora. - Вatorii Anastasia; Dobroer , Natalia; Сіренко, Лариса (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
Objective: The article aims to explore the cultural and historical influence of Odessa artists and intellectuals of the early 20th century who, after forming in the multicultural environment of Odessa, emigrated to Paris. It seeks to reveal how their creative contributions fostered the development of avant-garde art and helped preserve Ukrainian identity within the multicultural context of Paris. Methodology: This research utilizes an interdisciplinary approach that combines cultural, historical, and art analysis. A comparative method is applied to examine the work of Odessa artists in the context of the avant-garde movement, along with a cultural reconstruction method to recreate the socio-cultural environments of Odessa and Paris at the time. The study’s sources include archival documents, artworks, and contemporaneous critical reviews. Scientific Novelty: The study highlights the cultural phenomenon of the "Odessa Parisians" as representatives of the Ukrainian diaspora who, while preserving their national identity, contributed significantly to the formation of intercultural dialogue and avant-garde art in France. This research emphasizes Odessa’s unique role as a multicultural city, not part of the Russian cultural sphere but a key center of the Black Sea region, where the spirit of tolerance and cultural exchange flourished. Conclusions: The article underscores the importance of the Odessa art school in the history of the avant-garde movement and the role of Ukrainian artists who, despite the challenging conditions of emigration, continued to expand their creative potential within new cultural environments. It underscores that Odessa has been and remains a polyethnic and multicultural city, retaining its Ukrainian identity and standing outside the Russian cultural domain. Studying this phenomenon provides greater insight into contemporary intercultural processes, the role of the Ukrainian diaspora, and the importance of investigating historical and cultural contexts to counter contemporary propaganda narratives.